Citrato de rodio (II): síntese, caracterização, adsorção em nanopartículas de maguemita e preparação de fluidos magnéticos - Nunes, Eloiza da Silva (2010)
In this work are described the synthesis and characterization of dinuclear rhodium(II) citrate, adsorption study in maghemite nanoparticles, and preparation of nanoparticles-modified based magnetic fluids. Rhodium(II) citrate has significant antitumor activity being promissory to cancer chemotherapy. Due to the existence of free functional groups in its molecular structure this complex has capacity to functionalize iron oxide nanoparticles to produce drug-particles formulations. The modified nanoparticles show features of biocompatibility suitable to use the system in medical applications. Rhodium(II) citrate was synthesized by an exchange reaction of trifluoroacetate ligands from the precursor rhodium(II) trifluoroacetate by citrate ligands. The products were characterized by C and H elemental and thermogravimetric analysis, mass spectrometry, and infrared, UV/visible and 13C nuclear magnetic resonance spectroscopy. The results are consistent with the formation of dinuclear structure characteristic for rhodium(II) carboxylates. Changing the synthesis conditions were obtained products with stoichiometries [Rh2(H2cit)2(H2O)4] and [Rh2(H2cit)4(H2O)2]. The results and compounds solubility observations suggest that the first one occur as a coordination polymer. The second one showed composition e solubility behavior consistent with the formation of monomeric units. Maghemite nanoparticles with size mean between 5 and 7 nm were obtained through alkaline coprecipitation of Fe2+ and Fe3+ ions with further oxidation with oxygen gas. The solids were characterized by X-ray difratometry and the Scherrer relation was use to calculate the crystallite size mean. Adsorption experimental data were adjusted to Langmuir model and linear coefficients obtained, R2, were greater than 0,99. Functionalized nanoparticles were dispersed into water producing a stable colloid. Dispersion s characterization was performed by absorbance, zeta potential, and hydrodynamic diameter measurements. Surface properties and colloidal behavior of functionalized nanoparticles are much affected by adsorbed species. The colloidal stability of the magnetic fluids is dependent on the adsorbed amounts of rhodium(II) citrate and pH. When the adsorbed amount of rhodium(II) citrate is next to saturation, the magnetic fluids are stable in pH over 3 and show hydrodynamic diameter around 60 nm. Fluids colloidal stability is preserved against physiologic saline solution, PBS buffer, and fetal bovine serum over a period of 30 days.